Minimizing Fresh Fruit Bunches Inventory Costs Using Continuous Review System and Blanked Order System Methods - Galuh Amanda Sihotang; Ferida Azka Damiyati (Journal of Economics Business Industry, 2023)
PT X is a company engaged in palm oil processing. The company's inventory of FFB raw materials is erratic, depending on the production needs. In processing palm oil raw materials, companies in the logistics or inventory department cannot be separated from the problem of FFB raw material inventory, which is part of the primary needs for company production. This company faces issues, namely the fluctuation in demand and lead time for placing orders, which can cause stockouts and shortages in FFB raw material inventories, which disrupts production process activities. The purpose of the research conducted was to conduct an analysis of raw material inventory control using the continuous review system and blanked order system methods to avoid the occurrence of raw material shortages in the raw material inventory to be used and to minimize the total inventory costs that must be incurred at the company and determine the best inventory method. The results obtained from this study were getting a safety stock of 1,638 tons and a known reorder point of 5,093 tons for the schedule of reordering FFB raw materials using the continuous review system method. Based on the results of calculating inventory costs using the constant review system method, it is the most optimal method with a minimal total inventory cost compared to the blanked order system method and the previous company policy, with savings generated by 0.10%.